Relationship Between Heart Rate, Physical Activity, Sleep, Autonomic Nervous System and Motor Performance in 5-6-Year-Old Children Measured Continuously For 24 Hours - Yamate, Takafumi; Takigawa, Koji; Kozaki, Ryosuke; Abe, Keiko; Mimura, Kanichi (European Journal of Applied Sciences, 2024)
In this study, kindergarten children aged 5-6 years were subjected to a motor performance test and to continuous 24-hour measurement using a multifunctional wireless holter recorder to obtain basic physiological data on heart rate, physical activity, sleep information, and autonomic nervous system activity, and to examine the relationship between these data and motor performance. In the motor performance tests, boys showed higher values than girls in the 25-m run, standing long jump, and hard tennis ball throw. The total heart rate and mean heart rate upon awakening were significantly correlated with the 25-m run. Boys showed significantly higher basal metabolism, physical activity, fat burning and total energy consumption than girls, and significant correlations were also found between the 25-m run and the hard tennis ball throw. The number of times boys got up from sleep was significantly higher than that of girls. Concerning 25-m running, jumping over both feet, and catching the ball, the right side of the body showed significant correlations, while body support duration was significantly correlated with the number of arousals. Autonomic nervous activity during sleep was divided into Pattern 1 (standard type, with low sympathetic and high parasympathetic activities), Pattern 2 (sympathetic and parasympathetic activities alternating evenly), and Pattern 3 (opposite of standard type). Boys who excelled in running, jumping, and throwing also tended to excel in physiological data, suggesting the importance of early childhood athletic play.